Migration, health knowledge and teenage fertility: Evidence from Mexico - Marianna Battaglia (SERIEs - Journal of the Spanish Economic Association, 2015)
Migrationmay affect fertility and child health care of those remaining in the country of origin.Mexican data show that having at least one household member who migrated to the United States decreases the occurrence of pregnancy among teenagers by 0.339 probability points. This finding can be partially explained by the fact that teenagers in migrant households have a higher knowledge of contraceptive methods and likely practice active birth control. I use potential migration, measured as historic migration rates interacted with the proportion of adult males in the household, as an instrument to account for the endogeneity of migrant status.
Keywords: O15; J13; I12; 330; Migration; Fertility; Health knowledge